Program sistem penalti: Kaedah alternatif bagi pengurusan disiplin pelajar - Khalim Zainal,; Rohani Ahmad Tarmizi,; Zakaria Kasa,; Mizan Adiliah Ahmad Ibrahim, (penerbit ukm, 2007)
The purpose of this study was to investigate the effectiveness of the Penalty System Programme (PSP) which was introduced in Selangor and a comparison was made with the Conventional Discipline Programme (CDP) which is widely used in Malaysian schools. The Penalty System Programme which was implemented in Selangor used penalty points in managing disciplinary problems.The design of this study is ex-post facto. Findings revided that there exist significant difference between PSP and CDP for the aspect of vandalism (t = 3.949, p < 0.05), truancy (t = 5.117, p < 0.05), tardiness (t = 4.446,p < 0.005) and other diciplinary problems (t = 3.766, p < 0.05) but there is no significant difference for the aspect of discipline management in general. Overall findings shows that PSP is more effective in managing discipline in schools as compared to CDP.